Development and performance testing of a light weight portable solar rice cooker in rural areas of Bangladesh - Ahamed, R.; Kaderi, Mohd Arifin; Rashid, Muhammad Mahbubur; Ferdaus, Mohammad Meftahul (Universiti Malaya, 2014)
Generally sunlight is one of the most potential sources of energy on earth. Among the total energy consumption, energy consumption for cooking is a leading component in developing countries. Most of the rural people in Bangladesh use biomass fuel for cooking such as wood, cow dung, jute sticks or other agricultural wastes. Hence, there is an attentive necessity for the improvement of alternative, suitable, cheap mode of cooking in Bangladesh. This paper presents the thermal performance of a light weight Portable Solar Cooker (PSC) using parabolic shaped umbrella with aluminum foil coating. An umbrella of 125 cm diameter was used as a frame of the portable cooker because it is more convenient to transport and its surface area is almost parabolic. The aluminum foil was attached to the inner side of the umbrella with white glue which acts as reflector plate. The focal length of the parabolic surface was 26.16 cm. The maximum temperature of the experimental water recorded was 98˚C at around 12 PM. The investigational time was from 10:00 AM to 01:00 PM. The cooking power and energy efficiencies of the PSC were in the range 37W to 149.3 W and 2.8 % to 11.59%, respectively.